New Geological and Structural Facts under the Lateritic Cover in Garga Sarali, Ndokayo (East Cameroon) Area, from Audiomagnetotellurics Soundings - Pepogo Man-mvele Augustin Didier; Ndougsa-Mbarga Théophile; Meying Arsène; Ngoh Jean Daniel; Mvondo-Ondoua Joseph; Ngoumou Paul Claude (International Journal of Geophysics)
New geological and structural facts have been identified under the auriferous lateritic cover in Garga Sarali, Ndokayo area. Data were collected using AMT receiver system with frequencies ranging from 20 Hz to 50000 Hz. It consists of 16 AMT stations along 03 profiles, over Pan-African formations of East Cameroon. The wide frequency range enabled us to probe deep into the subsurface to obtain necessary information. Using Imagem software, coherency of data has been evaluated and only the data with a coherency below or equal to 0.7 have been considered. Two programs were used to map the subsurface. The pseudosections were obtained using IPI2WIN-MT, while geoelectrical sections were obtained using Stratagem Resistivity Plotter. Analysis of the curves of dimensionality tests shows that there is not always a complete superposition between the two telluric directions, translating the fact that the variation of the resistivity is not 1D, but rather 2D or 3D. Major features of 2D resistivity model from the respective profiles were identified. These features include a set of lower resistive formations going from the surface to 1000 m depth, lying on a set of resistive formations that appears at the surface and below the lower resistive formations. However, a very conductive layer was observed in depth in the three profiles. These facts show that the study area is made up of mixture of both conductive and resistive materials, suggesting a prolongation of the overlap between the Congo Craton and the Pan-African in depth to the north and the location of the CC/Pan-African limit above 4°N parallel accordingly. Deeper electrical discontinuities, interpreted as faults following a NE-SW trend, were highlighted. All these new data suggest that the study area underwent an intense tectonic activity with ductile to brittle deformations due to the presence of the BOSZ.